The main functional blocks of the test bench for the archival electronic documents validation - Melaschenko, A.O.; Perevozchikova, O.L.; Skarlat, O.S. (Інститут програмних систем НАН України, 2018)
The current legal framework regulating the electronic documents exchange in Ukraine does not determine the full electronic documents life-time, namely the electronic documents conformance assessment to the requirements for archival electronic documents. The purpose of the article is to detail the algorithm of archival electronic documents validation by means of the test bench. Motivated in the article is the necessity of the development of the archival electronic documents test bench, and the main principles of its functioning are considered. The test bench for archival electronic documents validation and the conformant national standards providing the file format for archival electronic documents – are the basis for the creation of the management subsystem for archival electronic authorized and reliable assets and would provide the long-term preservation.